Benefits of collaborative remembering in older and younger couples: the role of conversation dynamics and gender. Issue 3 (16th March 2023) - Zhang, Huan; Liu, Yibei; Wang, Xin; Cui, Ziqian; Wang, Haiman; Liu, Xiping; Wagner, Ullrich; Echterhoff, Gerald
ABSTRACT: We experimentally explored whether and how conversation dynamics would benefit collaborative remembering in intimate couples over time. To this end, we ran a study with a three-factor mixed design with relationship type (couples vs. strangers) and age (older adults vs. younger adults) as between-participants variables, and remembering condition (collaborative vs. individual) as a within-participants variable. Thirty pairs of intimate couples (fifteen long-term relationship older couples, fifteen short-term relationship younger couples) and thirty pairs of corresponding stranger-pairs (including older strangers and younger strangers) were compared with respect to recall accuracy and conversation dynamics, specifically considering the role of gender. Results revealed significant collaborative facilitation only in older couples. Also, females' communication behaviours facilitated males' collaborative remembering performance only in older (vs. younger) couples. In addition, a gender-specific pattern of shifts from the individual to collaborative context emerged only in older couple (vs. strangers). The findings are consistent with the notion that a longer experience of collaboration and more effective conversation dynamics allow older (vs. younger) couples to perform better at collaborative remembering. We discuss processes underlying the observed gender differences, and the social and motivational implications of collaborative remembering.